Reappraising the Production and Transfer of Hydrogen Atoms From the Middle to the Upper Atmosphere of Mars at Times of Elevated Water Vapor. Issue 5 (19th May 2022) - Montmessin, F.; Belyaev, D. A.; Lefèvre, F.; Alday, J.; Vals, M.; Fedorova, A. A.; Korablev, O. I.; Trokhimovskiy, A. V.; Chaffin, M. S.; Schneider, N. M.
Abstract: Water escape on Mars has recently undergone a paradigm shift with the discovery of unexpected seasonal variations in the population of hydrogen atoms in the exosphere where thermal escape occurs and results in water lost to space. This discovery led to the hypothesis that, contradicting the accepted pathway, atomic hydrogen in the exosphere was not only produced by molecular hydrogen but mostly by high altitude water vapor. Enhanced presence of water at high altitude during southern spring and summer, due to atmospheric warming and intensified transport, favors production of H through photon‐induced ion chemistry of water molecules and thus appears to be the main cause of the observed seasonal variability in escaping hydrogen. This hypothesis is supported by the observation of large concentrations of water vapor between 50 and 150 km during the southern summer solstice and global dust events. Using a simplified yet representative air parcel transport model, we show that in addition to the formation of atomic hydrogen from water photolysis above 80 km, a major fraction of the exospheric hydrogen is formed at altitudes as low as 60 km and is then directly advected to the upper atmosphere. Comparing the injection modes of a variety of events (global dust storm, perihelion periods, and regional storm), we conclude that southern spring/summer controls H production and further ascent into the upper atmosphere on the long term with direct implication for water escape. Plain Language Summary: Numerous lines of evidence suggest that Mars' water inventory was much larger in the past than it is today. The loss of this inventory has been driven by the formation of hydrated minerals on the surface, as well as by the escape of water to space. The first part of the escape process comprises the formation of H atoms, which may escape the planet once they reach the uppermost layers of the atmosphere. Here, we investigate one mechanism by which the H atoms may reach these high altitudes: the breakdown of water molecules by solar ultraviolet photons in the middle atmosphere (60–70 km above the surface), and the posterior ascent of the newly formed H atoms to the upper altitudes. We use a model that reveals that this process is the dominant contributor of atomic H to the upper atmosphere during periods of strong atmospheric circulation. In particular, we find that this mechanism is most efficient during the spring/summer season in the Southern Hemisphere, when Mars is closest to the Sun. Given that this season occurs every Martian year, our calculations suggest that this process has been the dominant contributor to water escape in the long term. Key Points: We decipher hydrogen production and migration to Mars' upper atmosphere using a box model for a variety of elevated water vapor cases H atoms formed between 60 and 80 km supply a dominant fraction of hydrogen to the upper atmosphere Our results suggest that perihelion climate has a key role in the hydrogen transfer to the upper atmosphere overall